Expression of epstein-barr virus encoded nuclear antigen 1 in benign and malignant tissues harbouring EBV. Issue 11 (November 1996) - Oudejans, J J; Dukers, D F; Jiwa, N M; van den Brule, A J; Grässer, F A; de Bruin, P C; Horstman, A; Vos, W; van Gorp, J; Middeldorp, J M; Meijer, C J
Abstract : AIMS: To determine levels of expression of Epstein-Barr virus (EBV) nuclear antigen 1 (EBNA1) in benign and malignant tissues harbouring EBV in relation to EBNA1 promoter usage. METHODS: Expression of EBNA1 was investigated by means of immunohistochemistry using a mixture of two EBNA1 specific monoclonal antibodies, 1H4-1 and 2B4-1. The presence of EBV was detected by EBER1/2 RNA in situ hybridisation. Detection of promoter specific EBNA1 transcripts was by RT-PCR analysis. RESULTS: EBNA1 positive cells were detected in all 20 EBV associated B cell lymphomas, 18 of which had arisen in immunocompromised patients; in eight of nine EBV associated T cell lymphomas; in 11 of 27 EBV positive cases of Hodgkin's disease; and in reactive lymphoid tissue harbouring EBV, including four cases of infectious mononucleosis. A diffuse EBNA1 staining pattern was observed in most of the EBV associated B cell lymphomas and was comparable with the EBER1/2 staining pattern. In the T cell lymphomas the number of EBNA1 positive cells was usually considerably less than the number of EBER1/2 positive ones. RT-PCR analysis revealed that in tumours with restricted EBNA1 expression-that is, T cell lymphomas and Hodgkin's disease lesions, EBNA1 transcripts were usually generated only by the F/Q promoter, whereas in B cell lymphomas EBNA1 transcripts were usually generated by both the C/W and F/Q promoters. CONCLUSIONS: EBNA1 is expressed in all types of tissue harbouring EBV, but the level of expression varies greatly. This may be the result of differential promoter usage.